THE ROLE OF CULTURAL UNDERSTANDING IN TEACHING ENGLISH AS A SECOND LANGUAGE - Mutalova Mohinur Tolibjon qizi (Research Focus International Scientific Journal, 2024)
This study explores the critical role of cultural understanding in teaching English as a Second Language (ESL). As globalization increases intercultural interactions, ESL educators must incorporate cultural awareness into their teaching methodologies to enhance language acquisition and student engagement. The research highlights how cultural competence facilitates better communication, fosters inclusive learning environments, and addresses cultural biases that may impede learning. Through qualitative analysis of classroom practices and case studies, this article demonstrates the benefits of integrating cultural elements into ESL curricula. Findings suggest that culturally responsive teaching strategies not only improve linguistic proficiency but also promote mutual respect and understanding among diverse student populations.